Overexpression of L-Type Amino Acid Transporter 1 (LAT1) and 2 (LAT2): Novel Markers of Neuroendocrine Tumors - Barollo, Susi; Bertazza, Loris; Watutantrige-Fernando, Sara; Censi, Simona; Cavedon, Elisabetta; Galuppini, Francesca; Pennelli, Gianmaria; Fassina, Ambrogio; Citton, Marilisa; Rubin, Beatrice; Pezzani, Raffaele; Benna, Clara; et al. (PloS one, 2016)
6-18F-fluoro-L-3,4-dihydroxyphenylalanine (18F-FDOPA) PET is a useful tool in the clinical management of pheochromocytoma (PHEO) and medullary thyroid carcinoma (MTC). 18F-FDOPA is a large neutral amino acid biochemically resembling endogenous L-DOPA and taken up by the L-type amino acid transporters (LAT1 and LAT2). This study was conducted to examine the expression of the LAT system in PHEO and MTC. Real-time PCR and Western blot analyses were used to assess LAT1 and LAT2 gene and protein expression in 32 PHEO, 38 MTC, 16 normal adrenal medulla and 15 normal thyroid tissue samples. Immunohistochemistry method was applied to identify the proteins' subcellular localization. LAT1 and LAT2 were overexpressed in both PHEO and MTC by comparison with normal tissues. LAT1 presented a stronger induction than LAT2, and their greater expression was more evident in PHEO (15.1- and 4.1-fold increases, respectively) than in MTC (9.9- and 4.1-fold increases, respectively). Furthermore we found a good correlation between LAT1/2 and GLUT1 expression levels. A positive correlation was also found between urinary noradrenaline and adrenaline levels and LAT1 gene expression in PHEO. The increased expression of LAT1 is also confirmed at the protein level, in both PHEO and MTC, with a strong cytoplasmic localization. The present study is the first to provide experimental evidence of the overexpression in some NET cancers (such as PHEO or MTC) of L-type amino acid transporters, and the LAT1 isoform in particular, giving the molecular basis to explain the increase of the DOPA uptake seen in such tumor cells.